Antifungal activity of the bark and leaf oils of Cinnamomum verum J.S. Presl. alone and in combination against Various Fungi - Bushra Abdul Karim Moharm,; Ibrahim Jantan,; Jacinta Santhanam,; Jamia Azdina Jamal, (penerbit ukm, 2005)
The leaf and bark oils of Cinnamomum verum J.S. Presl. were examined for their antifungal activity against 6 dermatophytes (Trichophyton rubrum, T. mentagrophytes, T. tonsurans, Microsporum canis, M. gypseum and M. audouini), one filamentous fungi(Aspergillus fumigatus) and 5 strains of yeasts (Candida albicans, Ca. glabrata, Ca.tropicalis, Ca. parapsilosis and Crytococcus neoformans) by using the broth microdilution method. The antifungal activities of 4 standard compounds(cinnamaldehyde, eugenol, linalool and α-terpineol) which were major constituents in the oils were also investigated in an effort to correlate the effectiveness of the oils with those of the components of the oils. The combined antifungal effect of the oils against M.canis, M. gypseum and Cr. neoformans was investigated by the checkerboard assay. Isobolograms were constructed and Fractional Inhibitory Concentrations Index (FICI) were calculated to determine the combination effects between the oils. The chemical composition of the oils was analyzed by gas chromatography (GC) and gaschromatography- mass spectrometry (GC-MS). The oils showed strong activity against all the tested fungi with Minimum Inhibition Concentration (MIC) values ranging from 0.04 to 0.31 mg/ml. Cinnamaldehyde which was the most abundant component of the bark oil of C. verum showed the strongest activity against all the fungi studied. Based on the results of the assay on standard samples, it may be that the high levels of cinnamaldehyde and eugenol in the oils and in combination with the minor components could be responsible for the high antifungal activity of the oils. The antifungal effect of the leaf and bark oils of C. verum in combination against the tested fungi was not synergistic. However, the effect was additive against M. gypseum and antagonistic against Cr. neoformans and M. canis.